A competência informacional de graduandos de biblioteconomia da região sudeste: um enfoque nos processos de busca e uso ético da informação - Mata, Marta Leandro da [UNESP] (2009)
The demands of the current scene led to Librarianship to deepen and highlight some educational aspects of the area through the promotion and creation of information literacy programs. What can contribute to the development of independent individuals as for the search process and information use in an ethical way. To achieve this purpose, it is essential that the librarian dominates this knowledge. Thus, it was proposed to verify the information literacy of graduates Librarianship’s courses in the Brazilian southeast region. It was applied a questionnaire based on the patterns of Association of College and Research Libraries in other similar researches. The research was composed of 230 students from fifteen public and private Librarianship’s schools located in the southeast of the country. The results showed that the participants possess the information literacy in the following aspects: to define their information needs, in assessment of information, on use and understanding of ethical and legal issues that surround its use, assisting to the precepts of information literacy standards for higher education. They also demonstrated that participants have difficulties as for the identification of typology of information sources and in the description of the elements that compose the references. It is considered that, in general, the research participants have information literacy, being able to contribute to the development of individuals with regard to the search process and information use.